A new species in the genus Milnesium (Eutardigrada) from USA (North Carolina) - Bartels, Paul J.; Kayastha, Pushpalata; Bartylak, Tomasz; Mioduchowska, Monika; Dmuchowska, Wiktoria; Kaczmarek, Łukasz (Zootaxa, 2025)
During recent research on autofluorescence in tardigrades a new species of Milnesium was discovered on the campus of Warren Wilson College (North Carolina, USA). We provide an integrative description of this new species based on morphology and genetics (COI, 18S rRNA and 28S rRNA sequences). The new species has six peribuccal lamellae, a smooth cuticle (but with pseudopores) and [3-3]-[3-3] claw configuration. This is a very common cluster of characters in the genus, and we provide a differential diagnosis for 24 similar species from which the new species differs by some morphological and morphometrical characters in addition to genetic differences.